2010
DOI: 10.1007/s10433-010-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

The relation between personality and the realism in confidence judgements in older adults

Abstract: This study investigated the relation between personality factors, as measured by the Swedish version of the NEO-FFI questionnaire, and the realism in older adults' (aged 60-93 years, = 1,384) probability confidence judgements of their answers to general knowledge questions. The results showed very small effect sizes for the contribution of the personality variables to the fit between the proportion correct answers and the level of one's confidence judgements. Although personality differed somewhat within the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 39 publications
5
36
1
6
Order By: Relevance
“…It is important to note that studies with adult samples indicate limited or no relationships between con fi dence levels and personality factors which include this type of self-report questionnaire, for example, extroversion (e.g. Dahl et al 2010 ) . The only exception to this is the openness to experience dimension which shares a positive correlation of low to moderate size (rarely above .30) with these on-task, on-line measures of con fi dence (see Kleitman 2008 , for a review).…”
Section: Self-con Fi Dence As An Aspect Of Metacognitive Experiencesmentioning
confidence: 99%
“…It is important to note that studies with adult samples indicate limited or no relationships between con fi dence levels and personality factors which include this type of self-report questionnaire, for example, extroversion (e.g. Dahl et al 2010 ) . The only exception to this is the openness to experience dimension which shares a positive correlation of low to moderate size (rarely above .30) with these on-task, on-line measures of con fi dence (see Kleitman 2008 , for a review).…”
Section: Self-con Fi Dence As An Aspect Of Metacognitive Experiencesmentioning
confidence: 99%
“…Single MCI was defined by having at least one impaired test score in the cognitive domain, whereas multi-MCI was defined by having an impaired test score in multiple cognitive domains. Normative data were derived from a subsample of GÅS (n = 511) and from a sister study SNAC-Blekinge (n = 1,402) [22] and was created using a quantile regression method, this process has been described elsewhere [19]. Cognitive impairment was defined as having a score below the 7th percentile of test scores in the normative sample, taking age, sex, and education into account.…”
Section: Implementation Of MCI Criteriamentioning
confidence: 99%
“…Participants who score highly on the characteristics of openness to new experiences and extraversion tend to have higher confidence in their JOLs than those who score lower on these characteristics (Buratti, Allwood, & Kleitman, 2013). Relationships between extraversion and overconfidence (Dahl, Allwood, Rennemark, & Hagberg, 2010;Pallier, Wilkinson, Danthir, Kleitman, Knezevic, Stankov, & Roberts, 2002;Schaefer, Williams, Goodie, & Campbell, 2004) and openness and overconfidence (Dahl et al, 2010;Schaefer, Williams, Goodie, & Campbell, 2004) have also been observed. Older adults high in agreeableness and consciousness have stronger associations between their subjective memory ratings and objective memory performance, suggesting that older adults high in these personality factors monitor more accurately than those who are low in these factors (Hülür, Hertzog, Pearman, & Gerstorf, 2015).…”
Section: Individual-level Influences Of Monitoring Accuracymentioning
confidence: 85%
“…YAs higher extraversion, openness, and conscientiousness are overconfident in their predictions. OAs higher in agreeableness and conscientiousness have more accurate judgments Pallier et al, 2002;Schaefer et al, 2004;Dahl et al, 2010;Schaefer et al, 2004;Stankov & Kleitman, 2008;Burratti, Allwood, & Kleitman, 2013;Hülur, Hertzog, Pearman, & Gerstorf, 2015 Measuring correlations between scores on personality assessments and monitoring frequency may be an area of future study. YAs higher extraversion, openness, and conscientiousness may report less spontaneous monitoring.…”
Section: The Relationship Between Spontaneous Monitoring and Task Permentioning
confidence: 99%